Internet connectivity disruption in Afghanistan (Afghanistan) - Voidly (Voidly Global Censorship Index, 2026)
CRITICAL severity disruption detected in Afghanistan. Data sourced from IODA.
Network Disruption Incident ID: AF-2026-0044. Severity: critical. Confidence: 65%